Just plug in your points.
all work is shown and pictured
The given line is
The given point is
The slope of the given line is
We found this by comparing
If two lines are perpendicular, then one is the negative reciprocal of the other.
Hence the slope of the required line is
Using the point-slope formula or otherwise, we can find the required equation.
We substitute the slope and point to get:
I'm pretty sure the answer is y=-1/4x+6
Slope intercept form of line: y=4x+21
To make an equation perpindicular to that line the slope is made opposite to the original. So the slope of 4, since it's a whole number, would become a fraction, and since the slope of 4 is positive the perpindicular line will have a negitive slope. 4 goes to -1/4.
Then you just plug in the point (4,5) to find the y-intercept.
so your final answer is y=-1/4x+6
The equation of the given line, y = 3x - 2, is written in slope-intercept form:
... y = mx + b
where m represents the slope and b is the y-intercept.
Matching the form to the given equation, you see m = 3, and b = -2. The slope of the given line is 3.
The slope of a line perpendicular to it will be the negative reciprocal of this value
... slope of perpendicular line = -1/m = -1/3
For some new value of b, the equation of the perpendicular line can be written
... y = (-1/3)x + b
Filling in the values of the point coordinates, we can find the appropriate value of b.
... 4 = (-1/3)(3) +b
... 4 = -1 + b . . . . . . . simplify
... 5 = b . . . . . . . . . . add 1
Then the equation you want is ...
... y = (-1/3)x + 5
y=-1/3x+5 is the point slope form
The slope of any line perpendicular to it is m2=-1/m1=3/2
Since it passes through point (6,3) and the slope m2=3/2 is known, we use the point-slope form to define the new line:
y-y1=m(x-x1) where (x1,y1)=(6,3).
Substituting x1=6, y1=3 into the point slope form,
is the line perpendicular to y=-(2/3)x+2 passing through (6,3)
Check: y=(3/2)6-6=3 ok, and
slope = -2/3
perpendicular slope = 3/2 (opposite and reciprocal)
passing thru (6,3)
y = mx+b
3 = 3/2 (6) + b
b = 3 -9
y = 3/2x - 6
well what did you do it matters what you did : )